Synergistic effects between red phosphorus and alumina trihydrate flame retardant silicone rubber composites - Zhuo JL; Chen XL; Dong J; Jiao CM (Plastics, Rubber and Composites Macro molecular Engineering, 2013)
The synergistic flame retardant effects between red phosphurus (RP) and alumina trihydrate (ATH) in silicone rubber (SR) composites were evaluated using limiting oxygen index. UL 94 rating, cone calorimeter, thermogravimetric analysis and digital photographs. It has been found that the SR composite containing only ATH does not show good flame retardancy at 39.0 wt-;loading. The cone calorimeter results showed that the heat release rate, mass loss rate, mass and total heat release of SR/ATH/RP composites decrease greatly in comparison with the SR/ATH composites. The digital photographs demonstrated that 1.0 wt-;RP could promote the formation of the homogenous and compact char layer. Thus, a suitable amount of RP has synergistic effect with ATH in the flame retardant SR composite system.
Keywords: Alumina trihydrate; Flame retardant; Red phosphorus; Silicone rubber